What is the value of the product above?
Note: is the Euler totient function , is the Moebius function, and is the golden ratio.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great problem! Part 1 and 2 are definitely needed for this problem!
Suppose k = 1 ∏ ∞ ( 1 − ϕ n 1 ) k μ ( k ) − φ ( k ) = S We can log both sides to obtain ln S = ln k = 1 ∏ ∞ ( 1 − ϕ n 1 ) k μ ( k ) − φ ( k ) = k = 1 ∑ ∞ k μ ( k ) − φ ( k ) ln ( 1 − ϕ n 1 ) = k = 1 ∑ ∞ k μ ( k ) ln ( 1 − ϕ n 1 ) − k = 1 ∑ ∞ k φ ( k ) ln ( 1 − ϕ n 1 )
Since ϕ 1 < 1 , and using the fact that ϕ = 2 1 + 5 , we can derive that k = 1 ∑ ∞ k μ ( k ) ln ( 1 − ϕ n 1 ) − k = 1 ∑ ∞ k φ ( k ) ln ( 1 − ϕ n 1 ) = 1
I'm not going to show why here, since it is what part 1 and 2 of this question is about, and I don't wish to reveal the answer here.
Hence ln S = 1 , S = e